Evaluation of an O antigen enzyme-linked immunosorbent assay for screening of milk samples for Salmonella dublin infection in dairy herds. - Hoorfar, J (1995)
Levels of antibodies to the O antigens (O:1,9,12) of Salmonella dublin were tested in 1355 serum, 1143 cow milk and 160 bulk milk samples from dairy herds using an enzyme-linked immunosorbent assay (ELISA). In order to define the background reaction, milk samples from all lactating cows and serum samples from 9 animals were collected in each of 20 salmonellosis-free herds located on the island of Bornholm, where cattle salmonellosis has not been reported. Similar samples were collected from all stalled animals in 10 herds with recent (< 6 months) outbreaks of salmonellosis located in Jutland, where salmonella infection is enzootic. Using herd history of salmonellosis, herd location and clinical status of the herds as criteria, the optimal cutoff in the milk ELISA was determined as being at least 5% of the samples having optical density > 0.5, resulting in herd sensitivity of 1.0 and herd specificity of 0.95. While none of the sera in the herds from Bornholm was ELISA positive, 2 herds had a few reactors in the milk ELISA. Using the same cutoff, all but 1 bulk milk sample from 150 herds on Bornholm was ELISA-negative, and all 10 salmonellosis-positive herds from Jutland were ELISA-positive. A significant correlation was found between ELISA reactions in milk and in serum of cows (34% and 32% respectively, rs = 0.69, P < 0.001).(ABSTRACT TRUNCATED AT 250 WORDS)